Description of a new species of Bothinodroctonus Schedl, 1969 (Coleoptera: Curculionidae, Scolytinae) from Africa - Knížek, Miloš; Mandelshtam, Michail (Zootaxa, 2015)
A new species of Bothinodroctonus in the tribe Polygraphini is described from Gambia and Kenya. This is the first representative of the genus in Afrotropical region. A holotype based description contains also the intraspecific variety of the newly described species based on available specimens and differential diagnoses to species within the genus.